Inhibitory activity of Lagerstreomia speciosa extract against Candida albicans, Aspergillus fumigatus, and Aspergillus flavus - Agustina Dwi Retno Nurcahyanti, Merry Liliana, Sem Samuel Surja (Journal of Applied Pharmaceutical Science, 2024)
Resistance of antifungal therapeutics has been reported, for instance, azole antifungal against Candida and Aspergillus. The discovery of new antifungal agent is thus warranted. Lagerstreomia speciosa is a notable Asian medicinal plant with profound antidiabetic activity. We previously demonstrated that the plant extract and one of the active substances, corosolic acid, have potential inhibitory effects against methicillin-resistant Staphylococcus aureus and can potentiate cefotaxime. The current study investigated the antifungal activity of bark and leaf extracts against three clinical fungal isolates. Well diffusion and broth microdilution methods were employed to assess the antifungal activity of L. speciosa leaf and bark extracts against Candida albicans, Aspergillus fumigatus, and Aspergillus flavus isolated from patients in Jakarta. Candida albicans was susceptible to the leaf and bark extracts as evidenced by the inhibitory zone ≥ 20 mm and minimum inhibitory concentration (MIC) of the leaf extract was categorized as susceptible-dose dependent. Aspergillus fumigatus and A. flavus were also relatively susceptible to the leaf extract, while the MIC of the bark extract categorized as susceptible-dose-dependent against both fungus. Lagerstreomia speciosa is a potential antifungal agent with comparable activity to fluconazole; therefore, further bioassay-guided fractionation of both extracts is warranted to identify the antifungal compound.
Keywords: Lagerstreomia, Candida albicans, Aspergillus flavus, Aspergillus fumigatus, fluconazole, corosolic acid